A success story or a flawed example? The anatomy of the Turkish model for the Middle East. (2014) - Özdikmenli, İlkim and Ovalı, Şevket
Abstract: This article argues that it is fallacious to promote the Turkish democratic experience under the Justice and Development Party ( Adalet ve Kalkınma Partisi, AKP) as a model for the emerging Arab democracies. Despite the early political reformism of the AKP, an empirical analysis of the government's recent crackdown on basic rights and freedoms demonstrates that the "Turkish model, " defined as a marriage of Islam and liberal democracy, cannot respond to the demands of Arab reformers. In this regard, the article falls into three sections. In the first section, assets of the "Turkish model" according to various actors are examined, which casts doubt on the emancipatory discourse underlying the promotion of the model. The second section proposes the term "leader democracy"—or, more specifically, "Erdoğanism"—as a way of denoting the governmental structure of Turkey as of early 2014. The final section depicts the current Turkish democracy in terms of the state of checks and balances and of basic political and social rights.